Intervention program to increase awareness on risks of smoking among rural community in Malaysia - Minhat, Halimatus Sakdiah; Juni, Muhamad Hanafiah; Zainuddin, Huda (Community Health Society Malaysia, 2016)
Smoking remains one of the major public health problems and challenges in Malaysia. Despite the various anti-smoking campaigns and health promotion programs, the prevalence of smoking remains high among adult Malaysian citizens. This intervention program aimed to improve the level of knowledge related to risks of smoking among a rural community in Malaysia. The program was conducted based on a considerably high prevalence of smoking and poor level of knowledge related to risks of smoking in a community health survey among the targeted rural population. The intervention involved dissemination of knowledge related to risks of smoking through posters exhibition, multimedia video, health talk and also consultation, which are example of self-help intervention program. A 3-point likert scale questionnaire, consisted of 10 items on risks related to smoking was distributed before and after the intervention to measure the level of knowledge of the respondents. A total of only 25 sets of completed pre and post intervention questionnaires were analysed. The analysis revealed significant difference of mean score obtained for knowledge before and after intervention (p=0.006), reflecting the effectiveness of the intervention program conducted. However, future similar intervention program should consider involvement of a bigger scale respondent. Such programs need to be repeated at certain intervals in order to sustain the related knowledge and also to create a better awareness on the harm effect of smoking. Relevant authorities should take the opportunity to evaluate the effectiveness of the health promotion programs rather than keep delivering the knowledge without knowing whether the conveyed messages are being digested accordingly.